2023
DOI: 10.1111/jsr.14035
|View full text |Cite
|
Sign up to set email alerts
|

The European Insomnia Guideline: An update on the diagnosis and treatment of insomnia 2023

Dieter Riemann,
Colin A. Espie,
Ellemarije Altena
et al.

Abstract: SummaryProgress in the field of insomnia since 2017 necessitated this update of the European Insomnia Guideline. Recommendations for the diagnostic procedure for insomnia and its comorbidities are: clinical interview (encompassing sleep and medical history); the use of sleep questionnaires and diaries (and physical examination and additional measures where indicated) (A). Actigraphy is not recommended for the routine evaluation of insomnia (C), but may be useful for differential‐diagnostic purposes (A). Polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 266 publications
0
10
0
Order By: Relevance
“…That is, even after optimal treatment, a considerable number of patients remain symptomatic or do not benefit at all. In case of insufficient response to CBT-I, according to evidence-based guidelines, medication with benzodiazepines (BZD), benzodiazepine receptor agonists (BZDRA), or sedating antidepressants can be offered [10]. Of note, remission rates of CBT-I combined with medication are comparable to those for CBT-I alone [9].…”
Section: Introductionmentioning
confidence: 99%
“…That is, even after optimal treatment, a considerable number of patients remain symptomatic or do not benefit at all. In case of insufficient response to CBT-I, according to evidence-based guidelines, medication with benzodiazepines (BZD), benzodiazepine receptor agonists (BZDRA), or sedating antidepressants can be offered [10]. Of note, remission rates of CBT-I combined with medication are comparable to those for CBT-I alone [9].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia manifests as challenges in falling asleep, maintaining sleep, or achieving restorative sleep. This condition is accompanied by notable symptoms, including fatigue, decreased concentration, impaired cognitive function, irritability, anxiety, and depressed mood [ 1 , 2 , 3 , 4 , 5 ]. The onset of insomnia could be associated with certain neurotransmitters, like γ-aminobutyric acid (GABA), 5-hydroxytryptamine (5-HT), and brain-derived neurotrophic factor (BDNF).…”
Section: Introductionmentioning
confidence: 99%
“…According to international guidelines, patient reported sleep diaries are important tools for assessing and treating insomnia [ 28 , 32 ]. They are used to gather subjective information on sleep and sleep habits that is not addressed by objective measures such as actigraphy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the clinical usefulness of the CSD have shown that the diary items are easy to understand, not too complex, and measure what they are intended to measure [ 12 , 24 ]. The CSD is recommended to be used in the clinical assessment of insomnia [ 32 ]. The CSD is available in two versions: a core version, consisting of nine questions on night related aspects of sleep, and an expanded version, consisting of 20 questions including questions on daytime related aspects of sleep.…”
Section: Introductionmentioning
confidence: 99%